Intraguild Predation Behaviour of Ladybirds in Semi-Field Experiments Explains Invasion Success of Harmonia axyridis - Raak-van den Berg, C. Lidwien (Public Library of Science, 2012)

(untitled)
Harmonia axyridis has been introduced as a biological control agent in Europe and the USA. Since its introduction, it has established and spread, and it is now regarded as an invasive alien species. It has been suggested that intraguild predation is especially important for the invasion success of H. axyridis. The aim of this study was to compare the intraguild predation behaviour of three ladybird species (Coccinella septempunctata, Adalia bipunctata, and H. axyridis). Predation behaviour was investigated in semi-field experiments on small lime trees (Tilia platyphyllos). Two fourth-instar larvae placed on a tree rarely made contact during 3-hour observations. When placed together on a single leaf in 23%–43% of the observations at least one contact was made. Of those contacts 0%–27% resulted in an attack. Harmonia axyridis attacked mostly heterospecifics, while A. bipunctata and C. septempunctata attacked heterospecifics as often as conspecifics. In comparison with A. bipunctata and C. septempunctata, H. axyridis was the most successful intraguild predator as it won 86% and 44% of heterospecific battles against A. bipunctata and C. septempunctata respectively, whilst A. bipunctata won none of the heterospecific battles and C. septempunctata won only the heterospecific battles against A. bipunctata. Coccinella septempunctata dropped from a leaf earlier and more often than the other two species but was in some cases able to return to the tree, especially under cloudy conditions. The frequency with which a species dropped did not depend on the species the larva was paired with. The results of these semi-field experiments confirm that H. axyridis is a strong intraguild predator as a consequence of its aggressiveness and good defence against predation from heterospecific species. The fact that H. axyridis is such a strong intraguild predator helps to explain its successful establishment as invasive alien species in Europe and the USA.